Rekonsepsi Penghitungan Kerugian Perekonomian Negara dalam Rangka Pembuktian Tindak Pidana Korupsi: Reconceptualizing the Calculation of National Economic Losses to Establish Evidence of Corruption - Miranda, Dita (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2025)
Corruption negatively affects the state's economy and undermines the national economy's stability. Law enforcement practices tend to emphasize tangible and measurable state financial losses, while losses to the national economy are often positioned merely as aggravating factors in sentencing. This study aims to examine the reconceptualization of the calculation of national economic losses in corruption cases. The research employs a normative juridical method with statutory, conceptual, and case approaches. The findings indicate that although court decisions have acknowledged the existence of national economic losses, the prevailing legal framework does not clearly regulate the authority or methodology for calculating such losses. This lack of clarity regarding authority and methodology creates normative ambiguity, resulting in legal uncertainty in proving corruption offenses. Therefore, a nationally standardized guideline for calculating national economic losses is necessary to ensure measurability, transparency, and inter-agency collaboration, as well as to guarantee consistency in judicial decisions in order to achieve legal certainty in the proof of corruption offenses.